2010
DOI: 10.1139/x10-065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two risk mitigation strategies for dealing with fire-related uncertainty in timber supply modelling

Abstract: We embedded a linear programming timber harvest scheduling model into an aspatial stochastic simulation model of a flammable forest to evaluate two fire risk mitigation strategies. The harvest scheduling model is solved repeatedly to produce harvest schedules within a rolling planning horizon framework. The risk mitigation strategies we examined were (1) whether or not to account for fire in the planning model and (2) replanning interval. We evaluated those strategies under four representative fire regimes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Consideration of HFR zonation provides the information necessary to integrate forest fire as a forest management constraint where it is a dominant ecological process in the landscape (Armstrong 2004;Gauthier et al 2009;Savage et al 2010). At the current scale of analysis, our HFR zonation may give a first although still rather coarse view of future fire regimes to fire and forest management agencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration of HFR zonation provides the information necessary to integrate forest fire as a forest management constraint where it is a dominant ecological process in the landscape (Armstrong 2004;Gauthier et al 2009;Savage et al 2010). At the current scale of analysis, our HFR zonation may give a first although still rather coarse view of future fire regimes to fire and forest management agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Such a shift in fire activity will greatly affect many interconnected ecological processes in the boreal forest, including the forest age mosaic, biodiversity patterns, and carbon balance (Amiro et al 2001;Flannigan et al 2005;de Groot et al 2009). These changes are expected to have a profound impact on fire and forest management strategies, notably by requiring a reduction in annual allowable cut volumes (Armstrong 2004;Savage et al 2010;Raulier et al 2013) and by substantially increasing the costs associated with forest protection and fire suppression (Wotton and Stocks 2006;Podur and Wotton 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Brumelle et al [66] made a survey of the literature on optimal forest management that took into account the presence of risk and found that 70% assumed risk neutral preferences and only 10% openly used risk averse preferences. A risk neutral forest manager would prefer adopting a strategy of passive acceptance whereas a risk adverse manager might prefer to adopt a risk mitigation strategy and continually revise his strategy in a dynamic replanning process [67]. Clearly, adopting a risk neutral strategy in the present case is an unsustainable strategy since important timber supply disruptions are to be expected (Figure 3), even with the present fire cycle of 400 years ( Figure 3a) and despite an expected success rate of 97% of the harvest plan implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Hyytiäinen and Haight (2009), for instance, evaluate even-and uneven-aged management systems for a single stand, using static annual burn probabilities and without considering possible impacts to adjacent stands. Savage et al (2010) embedded a non-spatial fire simulation model within a linear program harvest schedule model.…”
Section: Commercial Timber Lossmentioning
confidence: 99%